Strengthening the Capacity of Soetan Island Tourism Actors through Digitalization of Android Application-Based Tourism Services - Rivai, Harif Amali; Putra, Rahmat Eka; Syafrizal, Syafrizal; Adrianto, Fajri; Handika, Rebi Fara; Meidilisa, Velia; Wahyudi, Wahyudi (Warta Pengabdian Andalas, 2025)
This community service activity aims to support the development of digital-based tourism on Soetan Island, Pesisir Selatan Regency, by integrating tourism operators into an Android application. The application is designed as a transaction platform for booking tour packages offered by local operators, covering key destinations in the Mandeh Island area, particularly Soetan Island. Tourists can easily select and book various available tour packages, thereby expanding access and enhancing the region's tourism appeal. To support the implementation of this technology, a series of outreach and awareness-raising activities were conducted in stages with tourism operators. These activities aimed to provide a deeper understanding of the importance of digital information technology in managing and promoting tourism businesses. The methods used included a participatory approach through training, focus group discussions (FGDs), and direct technical assistance in using the application. The results of this activity were the development of an Android-based Soetan Island tourism application accessible to tourists, as well as increased understanding and readiness of local business operators to utilize digital technology as a strategic tool in tourism business development. This activity is expected to be the first step towards an inclusive and sustainable digital tourism ecosystem in the coastal areas of West Sumatra model.